2016
DOI: 10.1261/rna.058347.116
|View full text |Cite
|
Sign up to set email alerts
|

Erasure and reestablishment of random allelic expression imbalance after epigenetic reprogramming

Abstract: Clonal level random allelic expression imbalance and random monoallelic expression provides cellular heterogeneity within tissues by modulating allelic dosage. Although such expression patterns have been observed in multiple cell types, little is known about when in development these stochastic allelic choices are made. We examine allelic expression patterns in human neural progenitor cells before and after epigenetic reprogramming to induced pluripotency, observing that loci previously characterized by random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…That is, sample pairs generated from separate iPSC clones from the same subject were considered independent given our prior work showing allelic expression discordance in neural cultures derived from independent iPSC clones from the same donor 26 . This is consistent with the observation that many of the allelic effects on gene expression that occur in somatic cells are randomly reassigned in iPSCs after reprogramming and subsequent neural differentiation 35 .…”
Section: Methodssupporting
confidence: 90%
“…That is, sample pairs generated from separate iPSC clones from the same subject were considered independent given our prior work showing allelic expression discordance in neural cultures derived from independent iPSC clones from the same donor 26 . This is consistent with the observation that many of the allelic effects on gene expression that occur in somatic cells are randomly reassigned in iPSCs after reprogramming and subsequent neural differentiation 35 .…”
Section: Methodssupporting
confidence: 90%
“…Given that polyploidy and aneuploidy are linked to cancer progression and evolution, and appear to predict worse outcomes (Coward and Harding, 2014;Krajcovic and Overholtzer, 2012), it is possible that cancer cells benefit from increases in ploidy by increasing cellular diversity through stochastic allelespecific epigenetic and gene expression effects. Previous studies found that progenitor versus differentiated cellular states are associated with dramatic differences in RME, suggesting these mechanisms have roles in defining different cellular proliferative versus differentiated states (Miyanari and Torres-Padilla, 2013;Eckersley-Maslin et al, 2014;Gendrel et al, 2014;Jeffries et al, 2016;Branciamore et al, 2018;Ng et al, 2018). Recent studies have also begun to show how stochastic allele-specific epigenetic effects can interact with allele-specific genetic variants to create allelic diversity (Onuchic et al, 2018;Zhang S. et al, 2020).…”
Section: Stochastic Gene Regulatory Effects At the Allele Level As A Potential Driver Of Tumor Cell Diversity And Adaptabilitymentioning
confidence: 99%
“…Stochastic allelic switching has been found to be required for antigenic variation in Trypanosoma brucei parasites 18 , 19 . The study of clonal cell lineages has furthermore demonstrated that aASE can be acquired through development and differentiation and can be propagated to the clonal progeny of the cells 7 , 8 , 20 . However, recent advances in single cell genomics suggest that aASE effects are more dynamic even within near isogenic clonal cell lines 4 , 21 – 23 .…”
Section: Introductionmentioning
confidence: 99%